Aflatoxin Risk in Pepper Crops and Flaked Pepper in Southeastern Anatolia, Turkey - Hayrettin ÖZER; Fatma KAPLAN; Ayşin BİLGİLİ (ISPEC Journal of Agricultural Sciences)
The formation of aflatoxins in agricultural products, especially in peppers used as spices, has been determined that the products are affected by various stages from the field to the spice. These toxins are formed when fungi belonging to the genus Aspergillus spp. colonize the plant during the growing stage and produce aflatoxins. Post-harvest processes, especially drying and storage, significantly affect aflatoxin levels. Toxin accumulation can increase when drying processes are not carried out under appropriate conditions, while during storage, factors such as humidity and temperature can promote aflatoxin production. The aim of this study was to determine the risk of aflatoxin in pepper plants and chili peppers used as spices. Various aflatoxin species were detected in the analysis of samples taken from pepper fields and spice shops in Southeastern Anatolia, Turkey. While AFG1 and AFG2 were found in one of the 15 chili pepper samples, AFB2 was detected between 0.0125 and 0.1875 ppb in 11 samples and AFB1 was detected between 0.1125 and 3.95 ppb in 13 samples. Total aflatoxin content ranged from a minimum of 0.15 ppb to a maximum of 4.1375 ppb with an average of 0.9455 ppb. In addition, when the aflatoxin contents of Aspergillus spp. fungi obtained from pepper plants taken from the field were analyzed, the presence of AFB1 and AFB2 was detected in some samples. These findings suggest that aflatoxin formation starts at the growing stage of peppers and that harvesting, drying and storage processes can increase toxin levels. Therefore, these processes need to be carefully managed and controlled to minimize aflatoxin risk.